2017
DOI: 10.3389/fpsyg.2017.02174
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ Motor Proficiency and Statistical Learning for Actions

Abstract: Prior research has shown that infants learn statistical regularities in action sequences better than they learn non-action event sequences. This is consistent with current theories claiming that the same mechanism guides action observation and action execution. The current eye-tracking study tested the prediction, based on these theories, that infants’ ability to learn statistical regularities in action sequences is modulated by their own motor abilities. Eight- to eleven-month-old infants observed an action s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
0
10
1
Order By: Relevance
“…for instance, one screen-based experiment using action stimuli found anticipation rates of 20%-30% in toddlers (out of all gaze fixations), while a similar study using more complex visual stimuli with infants found anticipation rates of only 5% (Monroy et al, 2017b). In our study, infants were engaged in their own manual actions while monitoring those of their parents, and they were significantly less likely to anticipate when holding objects of their own.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…for instance, one screen-based experiment using action stimuli found anticipation rates of 20%-30% in toddlers (out of all gaze fixations), while a similar study using more complex visual stimuli with infants found anticipation rates of only 5% (Monroy et al, 2017b). In our study, infants were engaged in their own manual actions while monitoring those of their parents, and they were significantly less likely to anticipate when holding objects of their own.…”
Section: Discussioncontrasting
confidence: 46%
“…Infants become more precise at anticipating an observed action once they have acquired the requisite motor skill (Monroy et al, 2017b;Senna et al, 2016;Stapel et al, 2016), a finding that is not explained by general development. For instance, Monroy et al (2017b) took advantage of the natural variation in the emerging motor skills of young infants to show that those infants who had acquired a specific motor skill (e.g., a pincer grasp) were more precise at anticipating that action than infants of the same age who had not yet mastered that motor skill. Infants also demonstrate activation over their motor cortex when anticipating an action outcome (Monroy et al, 2019;Southgate et al, 2010).…”
Section: Linking Action Prediction 'In the Wild' To Other Developmental Processesmentioning
confidence: 98%
“…Additionally, researchers have identified links between action production and perception that are informative about the developing event segmentation system. Infants' prediction of others' action goals is linked to their developing ability to perform that same goal-directed action (Ambrosini et al, 2013;Filippi & Woodward, 2016;Kanakogi & Itakura, 2011;Monroy, Gerson, & Hunnius, 2017b;Sommerville, Woodward, & Needham, 2005;van Elk, van Schie, Hunnius, Vesper, & Bekkering, 2008; but see Gampe, Keitel, & Daum, 2015). Further, as indexed by suppression or attenuation of EEG alpha rhythms over sensorimotor cortical regions of the brain, infants' motor systems are activated when making predictions about others' goal-directed actions; this motor response does not apply broadly to tracking movements and is instead specific to actions for which a likely goal can be anticipated (Southgate, Johnson, Karoui, & Csibra, 2010).…”
Section: Developmental Change In Action Predictionsmentioning
confidence: 99%
“…); face discrimination (e.g.,Altvater-Mackensen, Jessen, & Grossmann, 2016;Dotsch, Hassin, & Todorov, 2016); action prediction (e.g.,Monroy, Gerson, & Hunnius, 2017; Schuwerk, Sodian, & Paulus, 2017); orthographic regularities Hex & Tong (2016); and natural images (e.g.,Denison, Sheynin, & Silver, 2017).Our label of "Other" SL methods spans a range of experimental approaches. Here, again, we offer a few characteristic examples.…”
mentioning
confidence: 99%